Fiscal Federalism and Endogenous Lobbies' Formation - Massimo Bordignon; Luca Colombo; Umberto Galmarini (Center for Economic Studies and ifo Institute (CESifo), 2003)
We study lobbying behavior by firms in a two-region economy, with either centralized or decentralized provision of profit-enhancing local public goods. Firms compete either in the market, lobbying for public good provision once entered in a market, or for the market, lobbying to gain ccess to it. When firms compete in the market, we show that lobbying is unambiguously less disruptive or social welfare under decentralization. Moreover, foreign rather than domestic private nterests may be more powerful in a.ecting regional policies. On the contrary, when firms compete or the market, lobbying is mostly e.ective under decentralization, since local firms always end p forming a local monopoly. However, we show that an institutional setting in which competencies re split between the center and the periphery may dominate either full centralization or full ecentralization or both.
Keywords: 330; fiscal federalism; lobbying; private interests